2010
DOI: 10.1016/j.visres.2010.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Reading speed in the peripheral visual field of older adults: Does it benefit from perceptual learning?

Abstract: Enhancing reading ability in peripheral vision is important for the rehabilitation of people with central-visual-field loss from age-related macular degeneration (AMD). Previous research has shown that perceptual learning, based on a trigram letter-recognition task, improved peripheral reading speed among normally-sighted young adults (Chung, Legge & Cheung, 2004). Here we ask whether the same happens in older adults in an age range more typical of the onset of AMD. Eighteen normally-sighted subjects, aged 55 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
89
2
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(105 citation statements)
references
References 87 publications
9
89
2
5
Order By: Relevance
“…Therefore, it would be likely that several age-related changes (not only declines, but also improvements) could be observed in reading. In fact, a few studies have shown an age-related decline in reading (Akutsu et al, 1991;Yu et al, 2010), although the effect has been less pronounced than those shown in other areas of visual performance. A recent study, on the other hand, reported that reading performance and contrast sensitivity for presbyopes were improved by perceptual learning without changing the optical characteristics of their eyes (Polat et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Therefore, it would be likely that several age-related changes (not only declines, but also improvements) could be observed in reading. In fact, a few studies have shown an age-related decline in reading (Akutsu et al, 1991;Yu et al, 2010), although the effect has been less pronounced than those shown in other areas of visual performance. A recent study, on the other hand, reported that reading performance and contrast sensitivity for presbyopes were improved by perceptual learning without changing the optical characteristics of their eyes (Polat et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…For example, Akutsu et al (1991) found that elderly participants who did not suffer from eye disease (60-74 years of age) read as fast as young participants for character sizes ranging from 0.3°to 1.0°. Yu et al (2010) reported that training to enlarge visual span could improve reading speeds for older adults as much as it did for young people, although several minor differences could be observed between the young and older groups. In contrast, the present study demonstrated that reading performance among the middle-aged was clearly degraded for the nearviewing condition (35 cm).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations